The Effectiveness of the Process of Investigating a Case of Illegal Levies in High School 2 of Ternate - La Tita; Tri Syafari; Nam Rumkel (Faculty of Law, Khairun University, 2019)
Illegal levies on Ternate High School 2 occur because of the active role of the Ternate High School 2 schools and the length of the process of disbursing School Operational Assistance (BOS) funds from the central government to regions for unexpected expenditure needs and funds that are not unexpected included in the BOS funds budget. This illegal levies case has been followed up at the investigation stage after a closed case process was carried out by the North Maluku Regional Police Special Criminal Investigation Investigator and from the results of the title it was concluded that the criminal element had been fulfilled by allegedly violating Article 12 letter (e) of the Law Number 20 of 2001 jo. Law Number 31 of 1999 concerning Eradication of Corruption. In addition, illegal levies have become individual behavior and have become a system of providing services to the community, as if these illegal levies have become prevalent.